PERLINDUNGAN HUKUM KREDITOR DENGAN OBJEK HAK GUNA BANGUNAN YANG BERAKHIR JANGKA WAKTUNYA SEBELUM PERJANJIAN KREDIT JATUH TEMPO - Lushun Adji Dharmanto (Jurnal Pembaharuan Hukum, 2016)
Expiry of broking which the credit agreement are not yet due date or the debtor has not paid off debts became a problem in banking, especially if the debtor in default, it will be detrimental to the creditors. Creditors need legal protection in order to obtain credit accounts back. Therefore, the law does not regulate legal protection against creditors which Broking as credit insurance has expired, while loans have not yet due date, so the bank can perform preventive efforts before credit is granted or act of anticipation.